Efficacy and safety of golimumab in patients with non-radiographic axial spondyloarthritis: a withdrawal and retreatment study (GO-BACK) - Weinstein, Cindy L J; Sliwinska-Stanczyk, Paula; Hála, Tomas; Stanislav, Marina; Tzontcheva, Anjela; Yao, Ruji; Berd, Yuliya; Curtis, Sean P; Philip, George (Rheumatology (Oxford, England), 2023)
OBJECTIVES: The GO-BACK study was designed to evaluate the efficacy and safety of golimumab (GLM) treatment withdrawal in adults with non-radiographic axial spondyloarthritis (nr-axSpA) who demonstrate inactive disease during a 10-month open-label (OL) GLM run-in. METHODS: Eligible participants received OL GLM in period 1. In period 2, participants who achieved inactive disease were randomized 1:1:1 to receive double-blind (DB) treatment with monthly placebo (PBO, treatment withdrawal) or continued GLM treatment given monthly (GLM QMT) or every 2 months (GLM Q2MT). Participants who did not have a disease flare continued DB treatment for ∼12 months. Participants with a disease flare discontinued DB treatment and resumed monthly OL GLM. Primary endpoint compared the proportion of participants without a disease flare in the continued GLM treatment groups (QMT or Q2MT) vs PBO in a multiplicity-controlled, step-down fashion. Safety follow-up continued for ∼3 months after last treatment. RESULTS: A total of 188 patients, out of the 323 enrolled, were eligible for participation in period 2. Both GLM QMT and GLM Q2MT were superior to treatment withdrawal (PBO) in preventing disease flare (P < 0.001), with a treatment-difference vs PBO of 50.4% and 34.4% for the GLM QMT and GLM Q2MT groups, respectively. The time-to-first flare was significantly longer (log-rank P < 0.0001) with GLM treatment compared with PBO. Of 53 participants (in Q2MT or PBO) who had a confirmed disease flare, 51 (96.2%) attained a clinical response within 3 months of restarting OL GLM. Adverse events were consistent with the known GLM safety profile. CONCLUSION: Among participants with active nr-axSpA who attained inactive disease after 10 months of GLM treatment, continued GLM treatment is well tolerated and provides superior protection against disease flares compared with GLM withdrawal. (EudraCT: 2015-004020-65, registered on 30 March 2022; NCT: 03253796, registered on 18 August 2017.).
Keywords: dvojitá slepá metoda; opakovaná terapie; Double-Blind Method; Retreatment; Non-Radiographic Axial Spondyloarthritis; safety; výsledek terapie; Symptom Flare Up; non-radiografická axiální spondyloartritida; Adult; efficacy; Humans; syndrom vzplanutí nemoci; non-radiographic axial spondyloarthritis; golimumab; withdrawal; dospělí; reduced dosing; Treatment Outcome; lidé